2005
DOI: 10.1128/aem.71.11.7483-7492.2005
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Mucin by Human Intestinal Bacteria and Establishment of Biofilm Communities in a Two-Stage Continuous Culture System

Abstract: The human large intestine is covered with a protective mucus coating, which is heavily colonized by complex bacterial populations that are distinct from those in the gut lumen. Little is known of the composition and metabolic activities of these biofilms, although they are likely to play an important role in mucus breakdown. The aims of this study were to determine how intestinal bacteria colonize mucus and to study physiologic and enzymatic factors involved in the destruction of this glycoprotein. Colonizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 57 publications
3
125
0
5
Order By: Relevance
“…Treatment vessels were dosed with 0. Results Total VFA, ammonia and lactate levels were found to be consistent between all vessels and values similar to previous studies (Macfarlane et al, 2005), with no significant treatment effects. qPCR analysis indicated a stable number of bacterial cells surviving in culture, comparable to in vivo values (Suchodolski, 2011).…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Treatment vessels were dosed with 0. Results Total VFA, ammonia and lactate levels were found to be consistent between all vessels and values similar to previous studies (Macfarlane et al, 2005), with no significant treatment effects. qPCR analysis indicated a stable number of bacterial cells surviving in culture, comparable to in vivo values (Suchodolski, 2011).…”
Section: Methodssupporting
confidence: 71%
“…Anaerobic conditions were maintained by bacterial fermentation and redox continuously measured. A sterile nutritive culture medium (Macfarlane et al, 2005) provided the fermentation substrates, supplied continuously by peristaltic pump to the vessels at 0.5 ml/min, with equal outflow. Treatment vessels were dosed with 0.…”
mentioning
confidence: 99%
“…53 Luminal mucosa-associated bacteria varied inter-individually, and showed intra-individual similarity on different sites of the colon. [54][55][56] The mucosa-associated bacteria are in close contact with/proximity to the epithelial cells, and therefore can have a major impact on these cells.…”
Section: Mucus and Mucin-associated Microbesmentioning
confidence: 99%
“…In an in vitro fermentation system mimicking the human intestine, Macfarlane et al reported that a heterogeneous bacterial community was colonizing mucin. 53 These authors used a combination of cultivation and visualization of the bacterial community by FISH, based on specific and general 16S rRNA probes. They observed that this community consisted of members of the Bacteroides fragilis group, bifidobacteria, enterobacteria and clostridia.…”
mentioning
confidence: 99%
“…signaling molecules produced by gram-negative bacteria, were identified in human feces of gastrointestinal disease patients as well as healthy subjects [13]. Moreover, bacterial quorum sensing molecules are likely to play a role in bacterial colonization of mucosa, thus requiring quorum sensingmediated biofilm formation [14]. Finally, Casula and Cutting showed the germination of Bacillus subtilis spores in the murine gastrointestinal tract, thereby probably requiring signaling peptides for quorum sensing pathway activation [15].…”
Section: Introductionmentioning
confidence: 99%